Analisis Pengaruh Jumlah Produksi Sepeda Motor dan Jumlah Tenaga Kerja Industri Komponen Sepeda Motor terhadap Gross Domestic Product Di Indonesia 1998-2003 - Reza Suriansha (Journal of Economics and Business UBS, 2020)
Japan's fourth largest motorcycle company in Indonesia are PT.Astra Honda Motor, PT.Yamaha Motor Kencana Indonesia, PT.Suzuki Indomobil and PT.Kawasaki Motor Indonesia, and have more than 90% market shares, which make them able to represent the entire motorcycle industry. Total production of the company is showing a positive trend towards Gross Domestic Product (GDP) of Indonesia from 1998 to 2003. In addition, motorcycle parts industry was important to the GDP of Indonesia because the industry requires the presence of components for assembly. This study aims to find out and analyze the linkages Indonesia's GDP from 1998 to 2003, the number of motorcycle production in four Japanese motorcycle companies in Indonesia and the amount of employment in the motorcycle parts industry. The data used are primary and secondary data. There are three hypotheses to be tested. These results prove that in fact the number of Japan's motorcycle production company affect Indonesia's GDP, and the number of Japan's motorcycle production company does not affect the amount of labor motorcycle parts industry significantly. In addition, the GDP did not affect the amount of labor motorcycle parts industry significantly. It is proven that there are some discrepancy between theory and practice.